2022
DOI: 10.1111/epi.17252
|View full text |Cite
|
Sign up to set email alerts
|

Seizure forecasting using minimally invasive, ultra‐long‐term subcutaneous electroencephalography: Individualized intrapatient models

Abstract: ObjectiveOne of the most disabling aspects of living with chronic epilepsy is the unpredictability of seizures. Cumulative research in the past decades has advanced our understanding of the dynamics of seizure risk. Technological advances have recently made it possible to record pertinent biological signals, including electroencephalogram (EEG), continuously. We aimed to assess whether patient‐specific seizure forecasting is possible using remote, minimally invasive ultra‐long‐term subcutaneous EEG.MethodsWe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Even if multimodal wrist-worn devices are unable to attain the performance of a brain implant, the ease of implementation, lower cost, broad applicability, and patient preference for a wrist-worn form factor 49 make this a critical area of study. Finally, future efforts should assess the utility of combining wearable and minimally invasive sub-cutaneous EEG 70 or intracranial EEG recordings. 69 This work provides evidence that long timescale cycles in noninvasive measures of human physiology are common in epilepsy, and that for many individuals, seizures occur at preferred phases of these cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if multimodal wrist-worn devices are unable to attain the performance of a brain implant, the ease of implementation, lower cost, broad applicability, and patient preference for a wrist-worn form factor 49 make this a critical area of study. Finally, future efforts should assess the utility of combining wearable and minimally invasive sub-cutaneous EEG 70 or intracranial EEG recordings. 69 This work provides evidence that long timescale cycles in noninvasive measures of human physiology are common in epilepsy, and that for many individuals, seizures occur at preferred phases of these cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Even if multimodal wrist-worn devices are unable to attain the performance of a brain implant, the ease of implementation, lower cost, broad applicability, and patient preference for a wrist-worn form factor 49 make this a critical area of study. Finally, future efforts should assess the utility of combining wearable and minimally invasive sub-cutaneous EEG 70 or intracranial EEG recordings. 69…”
Section: Discussionmentioning
confidence: 99%
“…• Annual reproductive counselling for women of childbearing age: 46% • Anxiety and depression screening: 55% • Risk advice on Sudden Unexpected Death in Epilepsy (SUDEP): 14% • In children: timely IV-benzodiazepine in status: 33% of available information in an increasingly complex era. Prof. Barbara Tettenborn (Cantonal Hospital St. Gallen, Switzerland) identified the main advantages as well as limitations of e-learning in neurology [5]. Though easily available and accessible, it often presents an abundance of information, which is not peerreviewed.…”
Section: Getting Evidence Into Practicementioning
confidence: 99%
“…Results of an open-label study with 263 migraine patients suggested that sTMS may be an effective, well-tolerated treatment option for migraine prevention [4]. A very recently published open-label study suggests that sTMS may be an effective, well-tolerated treatment option for the long-term prevention of difficult-to-treat, high-frequency episodic migraine and chronic migraine [5]. After 3 months, 93/153 (60%) analysed patients were responders.…”
Section: Targeting Cortical Activation By Transcranial Magnetic Stimu...mentioning
confidence: 99%
See 1 more Smart Citation